Blended learning model towards vocational students’ learning outcomes: A scoping review - Basori Basori; Sajidan Sajidan; Muhammad Akhyar; Wiranto Wiranto (Institute of Advanced Engineering and Science, 2023)
The learning characteristic in the 21st century is the availability of information anywhere and anytime. Blended learning (BL) became the most widely used learning strategy in vocational education. However, the problem is the effectiveness of BL on student outcomes. This scoping review provides an overview of the implementation of the BL model on vocational students. The research questions in this review were: i) What type of BL was taken?; ii) How did the BL model works?; and iii) What was improved in student learning outcomes? The research method adopted the scoping review from Arksey & Markey. From the beginning, the research article data was taken from the Scopus database. The article selection using the PRISMA method obtained 32 articles from 4,298 articles. The results of the review showed that there were three types of BL models. The three types of BL were: i) The flipped classroom model; ii) The station-rotation model; and iii) The self-blend model. BL syntax that teachers most favored in nine ways, but mainly with the syntax: “Face-to-face (F2F) finished, after that online learning for enrichment”. Meanwhile, most of the articles improved learning outcomes in the cognitive domain.